Changing Incidence, Outcome and Management of Myelomeningocele - J Gordon Millichap (Pediatric Neurology Briefs)
Pediatric neurosurgeons at Children’s Memorial Hospital, Chicago, review their long-term experience and the evolution of the etiology, diagnosis and management of patients born with myelomeningocele (MM) in 1975-1979 and followed for 25 years in a multi-disciplinary spina bifida clinic.